(untitled) (New York, 2017)
Little Leaders educates and inspires as it relates true stories of forty trailblazing black women in American history. Illuminating text paired with irresistible illustrations bring to life both iconic and lesser-known female figures of Black history such as abolitionist Sojourner Truth, pilot Bessie Coleman, chemist Alice Ball, politician Shirley Chisholm, mathematician Katherine Johnson, poet Maya Angelou, and filmmaker Julie Dash.
Keywords: Phụ nữ trong đời sống xã hội,Women in social life,Người nổi tiếng,Celebrities; Tiểu sử,Biography